Design and Performance Analysis of a Novel Asymmetrical Multilevel Inverter Structure With Reduced Components Using the Half-Height Modulation Technique - Naznin Sultana Tuhin; Yeasir Arafat (International Transactions on Electrical Energy Systems)
This paper presents a novel single-phase 37-level asymmetrical multilevel inverter with fewer components and less voltage stress at the switches which reduces the cost of the inverter and increases efficiency. Existing multilevel inverters utilize a higher number of components to provide better output quality which increases the cost and the complexity. The proposed inverter circuit generates 37 levels of output voltage by utilizing only four DC sources and thirteen IGBT switches. Reduction of the total harmonic distortion (THD) and improvement of the output quality of the proposed structure are performed by implementing the half-height modulation technique. The number of components, cost factor, THD, and efficiency of the proposed structure have been compared to those of the inverter structures that are currently in use. The performance of the proposed structure is evaluated by MATLAB/Simulink and simulation results show that the proposed circuit produces higher-level output voltage with reduced THD by utilizing less components/levels and low-rated devices which makes the proposed topology cost-effective and efficient compared to other existing topologies. Also, the proposed structure offers stable performance under a variety of load conditions. Multiple input sources and less distorted output of the proposed topology make it appropriate for renewable energy generating systems which contribute to the reliable, efficient, and sustainable generation of electricity.